Glycated Hemoglobin (HbA1c) as a Predictor of Periodontal Disease Progression in Patients with Type 2 Diabetes: A Longitudinal Study in Surabaya, Indonesia - Alexander Mulya; Muhammad Ashraf; Muhammad Yoshandi; Ayesh Mahmood; Daphne Marshall (Sriwijaya Journal of Internal Medicine, 2025)
Introduction: Periodontal disease is a prevalent complication of type 2 diabetes mellitus (T2DM), and poor glycemic control is a known risk factor. This longitudinal study aimed to investigate the predictive value of glycated hemoglobin (HbA1c) for periodontal disease progression in a cohort of T2DM patients in Surabaya, Indonesia. Methods: A prospective cohort study was conducted at private hospital, Surabaya, Indonesia, from January 2021 to January 2023. 180 patients with T2DM and pre-existing chronic periodontitis were enrolled. Periodontal parameters, including probing pocket depth (PPD), clinical attachment loss (CAL), bleeding on probing (BOP), and plaque index (PI), were assessed at baseline, 12 months, and 24 months. HbA1c was measured at each visit. Multivariate linear regression and mixed-effects models were used to analyze the association between HbA1c and changes in periodontal parameters over time, adjusting for potential confounders. Results: The mean age of participants was 58.5 ± 8.2 years, and 55% were female. Baseline mean HbA1c was 8.2 ± 1.5%. After adjusting for age, gender, smoking status, diabetes duration, and baseline periodontal parameters, higher baseline HbA1c was significantly associated with greater increases in PPD (β = 0.15 mm per 1% HbA1c increase, 95% CI: 0.08-0.22, p < 0.001) and CAL (β = 0.18 mm per 1% HbA1c increase, 95% CI: 0.10-0.26, p < 0.001) over 24 months. Furthermore, sustained elevation of HbA1c (average HbA1c over 24 months) was a stronger predictor of periodontal disease progression than baseline HbA1c alone. A significant interaction between HbA1c and time was observed (p < 0.001), indicating that the effect of HbA1c on periodontal parameters increased over time. Conclusion: HbA1c is a significant independent predictor of periodontal disease progression in patients with T2DM. Sustained glycemic control is crucial for preventing and managing periodontal complications in this population. These findings highlight the importance of interdisciplinary collaboration between internists and dentists in the comprehensive care of T2DM patients.